2007
DOI: 10.1016/j.oceaneng.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

On the tuning of a wave-energy driven oscillating-water-column seawater pump to polychromatic waves

Abstract: Performance of wave-energy devices of the oscillating water column (OWC) type is greatly enhanced when a resonant condition with the forcing waves is maintained. The natural frequency of such systems can in general be tuned to resonate with a given wave forcing frequency. In this paper we address the tuning of an OWC seawater pump to polychromatic waves. We report results of wave tank experiments, which were conducted with a scale model of the pump. Also, a numerical solution for the pump equations, which were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The whole problem (the simulation of the movements of the inner free surface due to the excitation of the outer sea-waves) is split into two sub problems: an outer one, dealing with the incident, diffracted and radiated waves, solved once for all, and an inner one, concerning the inner water volume behavior. The tuning of an OWC sea-water pump to polychromatic waves was investigated (Godoy-Diana and Czitrom, 2007) to enhance the performance of OWC wave energy device within a resonant condition when the forcing wave maintained. The flow characteristics in the components of an oscillating water column (OWC) system used for the wave energy capture was predicted by a numerical modeling by using the FLUENT code (Marjani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The whole problem (the simulation of the movements of the inner free surface due to the excitation of the outer sea-waves) is split into two sub problems: an outer one, dealing with the incident, diffracted and radiated waves, solved once for all, and an inner one, concerning the inner water volume behavior. The tuning of an OWC sea-water pump to polychromatic waves was investigated (Godoy-Diana and Czitrom, 2007) to enhance the performance of OWC wave energy device within a resonant condition when the forcing wave maintained. The flow characteristics in the components of an oscillating water column (OWC) system used for the wave energy capture was predicted by a numerical modeling by using the FLUENT code (Marjani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Falcão [6] developed a theoretical analysis to describe the ocean wave energy absorption by a linear array of oscillating water columns of arbitrary geometry. Other fine aspects related with the operation of these devices and similar equipments were reported by Godoy-Diana and Czitrom [7] to study the tuning of a seawater pump driven by a oscillating water column, and more recently, Conde and Gato [8] clarified the role of the oscillat-ing water column on the dynamic characteristics of the airflow which is trapped inside a typical pneumatic chamber.…”
Section: Introductionmentioning
confidence: 66%
“…The above results are in concordance with the predictions of Figs. (7) and (8), since the maximum values of the work done satisfy also this condition. In those figures, when increases, the ocean wave frequency decreases and for this case, we have the maximum work generated by the compressed air.…”
Section: Numerical Predictions Of the Generated Workmentioning
confidence: 83%
See 1 more Smart Citation
“…Other studies have used ESSs to mitigate short-term voltage fluctuations. However, in these applications, it has been found that the rating of the ESSs increases as the installed WEC power increases [14][15][16]. In [17], supercapacitors were used to improve wave farm power output at laboratory installations.…”
Section: Introductionmentioning
confidence: 99%